The Penguatan Tata Kelola Administrasi Sekolah Berbasis E-Archives untuk Meningkatkan Akuntabilitas Sekolah dalam Implementasi Kurikulum Merdeka di SMK Swasta Se-Kabupaten Kendal - Nina Oktarina; Uswatun Hasanah; Dian Fithra Permana; Dante Alighiri; Anis Susanti; Basyirun (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
Good administrative governance in organizations, especially in educational institutions, is crucial to support data-driven governance and management of educational records. Currently, archive management in schools is not yet optimal, and the capacity to support documents for school accountability is still low. Key issues include difficulty retrieving documents, loss of documents, and lack of consistency in the use of filing systems. One of the main causes of this problem is the incompetence of archivists. Therefore, community service activities are carried out to enhance the knowledge and skills of school archivists at private vocational schools in Kendal Regency. This activity includes training, documentation and archival digitization practices based on national education standards. The activity targets 50 school archivists in the area, using methods such as lecture, question and answer, discussion, and practice. The assessment is carried out based on improving knowledge and skills. The results of this activity include articles in national magazines, media reports and video clips about this activity.